Who's the teacher now? Human-centered teaching in a digital world. - Coelho, J. V. (N/A, 2025)
In an era where artificial intelligence is reshaping every facet of work, learning and cognition, education stands at a decisive intersection. The World Economic Forum (2023, 2024) forecasts seismic shifts in skill requirements and job configurations within just a few years, accelerated by technologies increasingly capable of mimicking, automating, and enhancing human intellectual tasks. In this rapidly evolving context, the role of teachers is neither obsolete nor untouched, but rather, urgently called to evolve. While some fear educational dilution and ethical uncertainty, others envision a renaissance of pedagogical agency, augmented by digital innovation. This developmental paper examines the nuanced interplay between AI and education, questioning whether emerging tools can serve, not supplant, the cognitive and emotional depth of human-led instruction. Grounded in Vygotsky's socio-constructivist theories and framed through recent global policy efforts, it proposes that hybrid intelligence may not only fill gaps but redefine them, offering a more empathetic, responsive, and inclusive learning future.